Knowledge, Attitude and Practice (KAP) among Foreigner Food Handlers at Restaurants with Long Operating Hours in Lembah Klang, Malaysia - Shafizi, Abdul Wahab; Sahilah, Abd Mutalib; Chai, Lay Ching *; Razalee, Sedek (Faculty of Medicine and Health Sciences, 2024)
Introduction: Poor food handling practices in restaurants with long operating hours which is dominated by foreign food handlers that increase the risk of foodborne diseases. This study aims to measure the level of knowledge, attitudes and practices (KAP) and to compare practice face to face interview with observed food safety practices of foreign food handlers in long-operating hours restaurants in Lembah Klang. Methods: This study was a cross-sectional study used face to face interviewer-assisted questionnaires with 117 foreign food handlers. A checklist guided observation was used to identify the actual practice status of 14 respondents. Results: There were no significant differences (p > 0.05) between sociodemographic characteristics and knowledge, attitudes and practices of food handlers. The mean score of knowledge, attitude and practice were 66.00 ± 13.67, 79.56 ± 16.67 and 66.02 ± 16.05 respectively. A weak and significant correlation (p < 0.01) between mean score of knowledge and attitude; knowledge and practice; and attitude and practice among foreigner food handlers (r = 0.287, r = 0.264, r = 0.285). The findings showed a significant difference (p < 0.001) between mean scores of practice face to face interview compared to observed practice (t = 5.467). Conclusion: Thus, this study demonstrated the food handlers had a good attitude toward food safety despite the moderate level of knowledge and practice that could be further improved. Meanwhile, actual practices that much affected by culture could be further improved with effective enforcement.